Efficacy of Metarhizium anisopliae in controlling the two‐spotted spider mite Tetranychus urticae on common bean in screenhouse and field experiments. (13th March 2014) - Bugeme, David Mugisho; Knapp, Markus; Ekesi, Sunday; Chabi‐Olaye, Adenirin; Boga, Hamadi Iddi; Maniania, Nguya Kalemba
Abstract The efficacy of aqueous and emulsifiable formulations of the fungus Metarhizium anisopliae isolate ICIPE78 was evaluated on the population density of Tetranychus urticae infesting common bean plants under screenhouse and field conditions. Synthetic acaricide abamectin was included as a check. Bean plants were artificially infested with T. urticae and allowed to multiply. Three treatments were applied in the screenhouse and 1 treatment in field trials. Mite density was recorded 2 d before spraying and weekly postspraying. The number of pods per plant, number of seeds per pod, and the dry weight of seeds per plant were recorded only in the screenhouse trials. In both screenhouse and field trials, fungal formulations applied at the concentration of 108 conidia/mL and the acaricide reduced the population density of mites as compared to the controls. There were significant differences in T. urticae population densities between the treatments at the various post‐spraying sampling dates. In the screenhouse, the mite densities were near zero from 3‐week postspraying in the treated leaves. At 4‐week postspraying, there were no more leaves in the untreated control (T1) and in the control water + Silwet‐L77 (T2). Fungal formulations were as effective as abamectin in reducing mite densities in both screenhouse and field experiments. There were significant differences in the production parameters during the 2 screenhouse trials, with fungal and abamectin treatments generally having the highest yield. Results of this study underline the potential of the M. anisopliae isolate ICIPE78 as an alternative to acaricides for T. urticae management.